A comparison between porcine, ovine, and bovine intervertebral disc anatomy and single lamella annulus fibrosus tensile properties. (12th November 2015) - Monaco, Lauren A.; DeWitte‐Orr, Stephanie J.; Gregory, Diane E.
ABSTRACT: This project aimed to compare gross anatomical measures and biomechanical properties of single lamellae from the annulus fibrosus of ovine and porcine lumbar vertebrae, and bovine tail vertebrae. The morphology of the vertebrae of these species differ significantly both from each other and from human, yet how these differences alter biomechanical properties is unknown. Geometric parameters measured in this study included: 1) absolute and relative intervertebral (IVD) and vertebral body height and 2) absolute and relative intervertebral disc (IVD) anterior‐posterior (AP) and medial‐lateral (ML) widths. Single lamella tensile properties included toe‐region stress and stretch ratio, stiffness, and tensile strength. As expected, the bovine tail IVD revealed a more circular shape compared with both the ovine and porcine lumbar IVD. The bovine tail also had the largest IVD to vertebral body height ratio (due to having the highest absolute IVD height). Bovine tail lamellae were also found to be strongest and stiffest (in tension) while ovine lumbar lamellae were weakest and most compliant. Histological analysis revealed the greatest proportion of collagen in the bovine corroborating findings of increased strength and stiffness. The observed differences in anatomical shape, connective tissue composition, and tensile properties need to be considered when choosing an appropriate model for IVD research. J. Morphol. 277:244–251, 2016. © 2015 Wiley Periodicals, Inc.